2015
DOI: 10.1038/aps.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the IL-37b gene elicits anti-tumor responses in mice bearing 4T1 breast cancer

Abstract: IL-37b exerts anti-4T1 breast carcinoma effects in vivo by modulating the tumor microenvironment and influencing T cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…In vitro studies further proved that rhIL‐37 directly promote CD4 + T‐cell proliferation. These results suggested an antitumor role of IL‐37 in breast cancer, probably through activating T‐cell responses …”
Section: Il‐37 In Tumormentioning
confidence: 79%
See 3 more Smart Citations
“…In vitro studies further proved that rhIL‐37 directly promote CD4 + T‐cell proliferation. These results suggested an antitumor role of IL‐37 in breast cancer, probably through activating T‐cell responses …”
Section: Il‐37 In Tumormentioning
confidence: 79%
“…It would be interesting to investigate the IL‐1R8 expressions in various cancer types as downregulation of IL‐1R8 expression might serve as another possible mechanism for cancer cells to evade the IL‐37–mediated antitumor activity. Although IL‐37 could directly inhibit tumor cell growth, this direct inhibition was diminished in immune‐incompetent nude and SCID mice in murine fibrosarcoma and breast cancer models . These findings may lead to an unexpected fact that the in vitro direct effect of IL‐37 on tumor cell growth may not be sufficient for its antitumor role in vivo.…”
Section: Mechanisms Involved In Il‐37 Antitumor Effects and Future Pementioning
confidence: 99%
See 2 more Smart Citations
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%